2022
DOI: 10.3390/su14137890
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Indoor Air Quality Prediction into Healthy Building Design

Abstract: Healthy building design is an emerging field of architecture and building engineering. Indoor air quality (IAQ) is an inevitable factor that should be considered in healthy building design due to its demonstrated links with human health and well-being. This paper proposes to integrate IAQ prediction into healthy building design by developing a simulation toolbox, termed i-IAQ, using MATLAB App Designer. Within the i-IAQ, users can input information of building layout and wall-openings and select air pollutant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…This study aimed to develop a better understanding of this phenomenon by examining the previous literature and structuring research variables accordingly. The significance of indoor design parameters for airborne infection was emphasized, based on evidence from various scholars who have demonstrated the positive impact of indoor design on IAQ and their influence on user experience in the space and their reactions to the space [ [59] , [60] , [61] ]. IAQ factors such as ventilation rate, humidity, and CO₂ concentration are affected by design parameters and play a crucial role in the spread of airborne diseases [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study aimed to develop a better understanding of this phenomenon by examining the previous literature and structuring research variables accordingly. The significance of indoor design parameters for airborne infection was emphasized, based on evidence from various scholars who have demonstrated the positive impact of indoor design on IAQ and their influence on user experience in the space and their reactions to the space [ [59] , [60] , [61] ]. IAQ factors such as ventilation rate, humidity, and CO₂ concentration are affected by design parameters and play a crucial role in the spread of airborne diseases [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In other words, meteorological conditions can significantly impact indoor PM concentration levels, as they can affect the particle size depending on the indoor air exchange rate, relative humidity, and the origin of the air mass [ 45 , 46 ]. Therefore, it can be inferred that outdoor meteorological variables may be used to predict indoor PM 2.5 concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of indoor temperature, it was confirmed that a significant negative effect was given between 8–10H models, and the outdoor PM 2.5 concentration also showed a large weight between 7–10H models. Furthermore, as a result of checking the intercept, the 8–11H model appeared higher than other models, and it was found that the indoor PM 2.5 concentration appeared high during that time [ 45 ]. This is a result that can verify that there is an indoor source in the corresponding time.…”
Section: Discussionmentioning
confidence: 99%
“…In 2022 Shrestha et al [4] used CO 2 to evaluate the indoor air quality (IAQ) as an indicator in naturally ventilated Nepalese school buildings. Yang et al [5] used CO 2 as one of several indicators to predict the IAQ in healthy building design by developing a simulation toolbox named i-IAQ. Stabile et al [6] assessed the air quality in an Italian classroom by evaluating the CO 2 concentrations in relation to the energy usage of the ventilation system.…”
Section: Introductionmentioning
confidence: 99%